Dynamic mechanical and dielectric properties of modified surface chitosan/natural rubber latex - Wirach Taweepreda (Universiti Kebangsaan Malaysia, 2014)
Biodegradable polymeric films, obtained from chitosan/natural rubber latex (CS/NRL) blends with different compositions, have been prepared by wetting process. The blends were characterized by dynamic mechanical thermal analysis (DMTA) and found that the CS/NRL blends are thermodynamically incompatible. This is evident from the presence of two glass transitions, corresponding to CS and NRL phases in the blend. The mechanical properties of the CS/NRL blends were improved with increasing the amount of chitosan and after surface treatment with sulphuric acid due to the sulfonate ionic interaction. The dielectric properties was determined using Precision LCR meter in the frequency range 75 kHz up to 30 MHz. After CS/NRL surface treatment with sulphuric acid at high content of chitosan showed the highest dielectric constant. The surface properties of the CS/NRL blend films before and after surface treatment were confirmed by atomic force microscopy (AFM), respectively.